PENGARUH MEDIA BOARDBOOK HURUF HIJAIYAH TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA SEKOLAH DASAR - Nadinda Leony Putri; Supriyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the effect of using hijaiyah letter boardbook media on elementary school students' ability to read at the beginning. The research uses a quantitative approach with a pre-experimental research design and one group pretest-posttest design. There are two variables in the research, namely hijaiyah letter boardbook media and students' initial reading abilities. The population of this study were lower grade students in elementary schools with a sample of 25 people. Data collection techniques use initial tests and final tests. The analysis technique used to answer the objectives and test the hypothesis uses inferential statistical analysis techniques (paired t-test). The results of the research show that there is an influence of using hijaiyah letter boardbook media on initial reading abilities, where students have the ability to recognize and arrange letters into syllables, words and sentences.